Analyzing the Functional Features of VoLTE Service Using Robust Header Compression (ROHC) - بدر, يعرب; علو, علي (Latakia University Journal -Engineering Sciences Series, 2020)
LTE (Long Term Evolution) is a mobile broadband wireless technology developed by the 3GPP to respond to the greedy demand for low latency multimedia applications. For this reason, LTE performance evaluation and optimization directly becomes a hot topic for the scientific community. The focus of this research is on VoLTE (VoIP over LTE) and more specifically, to study the transport protocols of VoIP calls over LTE-4G cellular network considering different scenarios of congested and non-congested multimedia applications running on the same networks and exhaust the available bandwidth. The cheap cost of making an international VoIP call and paying only one bill is a great benefit. Although its significant advantages, VoIP technology have some known difficulties that becomes serious challenges in the 4G wireless environments such as packet loss, jitter and lips to ear delay. This nature of the wireless radio channel invokes several problems of QoS previously noted parameters and affects QoE satisfaction of the interested users. Up to this end, the examine presses of many software's and simulation platforms can be used to evaluate the performance of VoLTE. LTE-Sim is the best open source framework to evaluate LTE system and VoLTE scenarios. LTE-Sim permits to evaluate multi-cell/multi-users environments of scheduled devices in uplink and downlink. This simulator encompasses several aspects of LTE networks such as QoS management, user mobility, handover procedures, frequency reuse, radio resource optimization and other aspects. By applying the Robust Header Compression (ROHC) to VOIP packets and studying the system performance parameters referred to earlier, we can implement a congestion scenario in a LTE network consisting of 900 subscribers located near base stations and 300 remote subscribers. simulation results show that ROHC can be very effectively for near-piont subscribers versus negligible packet loss. For far-point subscribers ROHC is not recommended.